Racing performance and incremental double poling test on treadmill in elite female cross-country skiers - Fabre, N.; Balestreri, F.; Leonardi, A.; Schena, F. (The Journal of Strength and Conditioning Research, 2010)
The national Italian cross-country ski team has been evaluated on the basis of a new double poling cross-country roller skiing incremental test to exhaustion (DP) on a motorized driven treadmill. To verify the capacity of this specific test to predict performance, peak oxygen uptake (VO2peak), oxygen uptake at anaerobic threshold (VO2Th), peak treadmill speed, and treadmill speed at anaerobic threshold (Speak and STh, respectively) were measured during the test and correlated with the level of performance of 10 world class Italian female cross-country skiers. The physiological data obtained were also compared with results of an incremental and maximal test carried out by the same athletes but with the diagonal stride (DS) technique. Peak heart rate (HRpeak), HRTh, and VO2Th were significantly higher during DS than during DP (p < 0.001 for HRpeak and heart rate at anaerobic threshold (HRTh) p < 0.05 for VO2Th), whereas no difference was observed for VO2peak. Speak and VO2peak were significantly correlated to FISI points only during DP (r = -0.88, p < 0.001 and r = -0.77, p < 0.01, respectively). STh and VO2Th during DP and VO2Th during DS were correlated with the level of performance (r = -0.88, p < 0.001; r = -0.63, p < 0.05; and r = -0.65, p < 0.05, respectively). Finally, VO2peak DP/VO2peak DS ratio was also correlated to the performance (r = -0.77, p < 0.01). On the other hand, no peak value achieved during DS was correlated with the level of performance. Based on these physiological results, this incremental DP test to exhaustion appears like a good predictor of elite cross-country skiers' performance.